Effect of Granular Waste Compact Disc on Bond Strength between Steel Bars and Surrounding Concrete (Fracture and Structural Integrity, 2023)
In recent decades, researchers have tried to use waste materials as a partial or complete replacement of the gravel ingredients of concrete to reduce environmental impact. One of these materials is electronic waste. The problem of this disposal material, particularly outdated CDs and DVDs, has turned out to be serious. In this study, 36 pull-out cylindrical shape test specimens were used to conduct an ASTM C234-91A-compliant pull-out test to measure the bonding behavior and strength between three sizes of steel bars and concrete with different embedded lengths, including waste disc shreds (CD and DVD) as a partial substitute for fine aggregate. Four groups of modified concrete specimens with different percentages of disc shreds as partial replacements for sand were prepared. The ratio of cement:sand+disc:coarse aggregate:water was 1:2:2.5:0.4. The disc shreds were utilized to substitute partially for fine aggregate in four different weight percentages: 0%, 4%, 8%, and 12%; nevertheless, the cement-to-sand ratio was consistently 2. Results demonstrated that the bond strength is considerably influenced by the bar diameter and the disc shreds (CDs and DVDs) used as a partial replacement for fine aggregate. The bond strength behavior of the modified concrete with disc fibers is comparable with that of traditional concrete. The ACI-318 Code for the bond strength of ordinary Portland cement concrete was modified to calculate the bond strength of this new kind of disc concrete.
Keywords: Bond strength; CDs waste; DVDs waste; Modified concrete